Возможная природа сейсмической активности недр Преддобруджского прогиба и Северной Добруджи - Старостенко, В.И.; Бурахович, Т.К.; Кушнир, А.Н.; Аегостаева, О.В.; Цветкова, Т.А.; Шеремет, Е.М.; Шумлянская, А.А. (Геофизический журнал, 2013)
Переддобрудзький прогин і суміжні структури належать до частини мантії під Східноєвропейською платформою, визначеної змінами нульової ізолінії нев’язок швидкості з глибиною в межах верхньої мантії і її перехідної зони за даними 3D P-швидкісної моделі. Мантійній примежовій зоні відповідає система похилих шарів. Особливості швидкісної будови мантії під Переддобрудзьким прогином і суміжними структурами дають змогу виділити мантійні передумови сейсмічності цієї області, пов’язані з проявом мантійного плюму в нижній і середній мантії . Тривимірна глибинна геоелектрична модель , яка побудована за результатами сучасних досліджень методами МТЗ і МВП, відбиває неоднорідний розподіл питомого електричного опору в надрах регіону. Витягнуті на сотні кілометрів провідники приурочені до глибинних провідних розломів різного рангу і їх перетинів. У межах південного борту Переддобрудзького прогину виділено високопровідний шар складної конфігурації, який залягає на глибинах, що відповідають нижній корі і верхам верхньої мантії. Вогнища землетрусів, як і аномалії високої електропровідності, переважно відповідають розміщенню активних глибинних тектонічних розломів і зон зчленування різновікових геологічних структур. У інтервалі 28—30° сх. д. — 45—46° півн. ш. просторове розміщення аномалій електропровідності співвідноситься із зоною прояву глибинних мантійних флюїдів, що відповідають мантійному плюму. PeriDobruzha depression and its surrounding belong to border zone of the mantle under the EEP, distinguished by the changes of zero isoline of velocity discrepancies with the depth within the limits of the upper mantle and its transition zone according to the data of 3D P-velocity model. The system of inclined layers corresponds to mantle border zone. Special features of mantle velocity structure under PeriDobruzha depression and its surrounding made possible to partition mantle prerequisites of seismicity of the area under consideration related to manifestation of mantle plume in the lower and medium mantle. Three-dimensional deep geo-electric model constructed according to the results of modern studies by MTS and MVP methods reflects heterogeneous distribution of present electric resistance in the depth of the region. Extended for hundreds of kilometers conductors are confined to deep conducting faults of different rank and their intersections. High-conductivity layer of complicated configuration is distinguished at the southern flank of the PeriDobruzha depression and occurs at the depths corresponding to lower crust and upper parts of the upper mantle. The source of the earthquakes as well as the anomalies of high electro-conductivity are mainly corresponding to occurrence of active deep tectonic faults and connection zones of geological structures of different ages. Within the interval of 28—30° eastern longitude — 45—46° northern latitude spatial disposition of electric conductivity anomalies comply with the area of manifestation of deep mantle fluids corresponding to mantle plume. Преддобруджский прогиб и его окружение относятся к пограничной области мантии под ВЕП, определенной изменениями нулевой изолинии с глубиной в пределах верхней мантии и ее переходной зоны по данным 3D P-скоростной модели. Мантийной пограничной зоне соответствует система наклонных слоев. Проявление субвертикальной мантийной колонки объясняет сейсмическую активность проявлением мантийного сверхглубинного флюида и соответствующих ему наклонных слоев. Трехмерная глубинная геоэлектрическая модель, построенная по результатам современных исследований методами МТЗ и МВП, отражает неоднородное распределение удельного электрического сопротивления в недрах региона. Вытянутые на сотни километров проводники приурочены к глубинным проводящим разломам различного ранга и их пересечениям: Фрунзенскому, Саратскому, Болградскому, Кагульско-Измаильскому, Чадырлунгскому и другим. Высокопроводящий слой сложной конфигурации выделяется на Южном борту Преддобруджского прогиба и залегает на глубинах, соответствующих нижней коре и верхам верхней мантии. Очаги землетрясений, как и аномалии высокой электропроводности, в основном, соответствуют расположению активных глубинных тектонических разломов и зон сочленения разновозрастные геологических структур.